2018
DOI: 10.1093/jac/dky321
|View full text |Cite
|
Sign up to set email alerts
|

Does shared decision-making reduce antibiotic prescribing in primary care?

Abstract: SDM can be a framework to reduce the prescribing of antibiotics and thus to control antibiotic resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 24 publications
4
24
0
Order By: Relevance
“…This is supported by a study looking at drivers for the variability in the rate of antibiotic prescribing in UK general practices, which suggests that the influence of overall patient health in the decision to prescribe is limited, 20 and in the current study, where patients with similar risk profiles (such as Charlson scores) were also treated differently between different common infections. This variability in antibiotic prescribing after adjustment for age, gender and calendar time confirms that more consistent prescribing and optimization in decision making, such as shared decision making, could impact prescribing 40 and are essential if we are to reduce inappropriate overuse and thus avoidable resistance.…”
Section: Discussionmentioning
confidence: 72%
“…This is supported by a study looking at drivers for the variability in the rate of antibiotic prescribing in UK general practices, which suggests that the influence of overall patient health in the decision to prescribe is limited, 20 and in the current study, where patients with similar risk profiles (such as Charlson scores) were also treated differently between different common infections. This variability in antibiotic prescribing after adjustment for age, gender and calendar time confirms that more consistent prescribing and optimization in decision making, such as shared decision making, could impact prescribing 40 and are essential if we are to reduce inappropriate overuse and thus avoidable resistance.…”
Section: Discussionmentioning
confidence: 72%
“…The study of practice variation helps to pinpoint practices with high antibiotic prescribing to target interventions as well as practices with low antibiotic prescribing. This allows to find out which modifiable factors are associated with low and high antibiotic prescribing, such as the level of shared decision making that GPs use [ 24 ] or the rate of diagnostic testing [ 25 ]. The outcome of such a study could be used in the design of future interventions and in antimicrobial stewardship programs.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies conducted in non-US healthcare settings has found that shared decision making is effective and does not contribute to diverging from clinical guidelines. 18,22 Patient communication can be tailored to clearly delineate the role of the clinician as the prescribing decision maker with sensitivity to patient preferences that can result in a decision that is better understood by the patient. Patient education tools should increase transparency concerning the standard of care for ARI visits and support clinician decisions not to prescribe antibiotics unless truly necessary, such as those illustrated with public commitment posters.…”
Section: Discussionmentioning
confidence: 99%